2022
DOI: 10.2478/hukin-2022-0092
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Caffeinated Chewing Gum on Volleyball Performance in High-Performance Female Players

Abstract: To date, no investigation has studied the effect of acute intake of caffeinated chewing gum on volleyball performance. Therefore, the aim of this investigation was to establish the impact of caffeinated chewing gum ingestion on physical performance in female volleyball players. Twelve high-performance volleyball female athletes participated in a randomized, crossover, placebo-controlled, and double-blind experiment. Each athlete performed two identical experimental sessions after a) ingestion of ~6.4 mg/kg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
1
11
1
Order By: Relevance
“…The results of the current study showed no significant impact of caffeine via chewing gum on attack and block jumps. Surprisingly, the results of the current study are inconsistent with previous investigations [ 16 , 22 ] in which caffeine supplementation had a positive effect on those volleyball jumps. In a study by Pérez-López et al [ 16 ], caffeine at a dose of 3 mg/kg BM via energy drink contributed to the increase in height and peak power in attack and block jumps, which were performed according to the same procedure as in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The results of the current study showed no significant impact of caffeine via chewing gum on attack and block jumps. Surprisingly, the results of the current study are inconsistent with previous investigations [ 16 , 22 ] in which caffeine supplementation had a positive effect on those volleyball jumps. In a study by Pérez-López et al [ 16 ], caffeine at a dose of 3 mg/kg BM via energy drink contributed to the increase in height and peak power in attack and block jumps, which were performed according to the same procedure as in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study by Pérez-López et al [ 16 ], caffeine at a dose of 3 mg/kg BM via energy drink contributed to the increase in height and peak power in attack and block jumps, which were performed according to the same procedure as in the present study. Moreover, the study by Filip-Stachnik et al [ 22 ] showed an improvement in attack jumps before and after the simulated game after supplementation of caffeinated gum at a dose of ~6 mg/kg BM. The reason for the lack of improvement in attack and block jump after caffeine supplementation observed in the current investigation might be associated with the sports level of participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations